Kinetic analysis reveals the diversity of microscopic mechanisms through which molecular chaperones suppress amyloid formation - Paolo Arosio (Nature Portfolio, 2016)
Molecular chaperones are recognized to interfere with protein aggregation, yet the underlying mechanisms are largely unknown. Here, the authors develop a kinetic model that reveals the variety of distinct microscopic mechanisms through which molecular chaperones act to suppress amyloid formation.